1988
DOI: 10.1086/185155
|View full text |Cite
|
Sign up to set email alerts
|

Warm ultraluminous galaxies in the IRAS survey - The transition from galaxy to quasar?

Abstract: Of 90 extragalactic objects chosen from the I RAS catalog on the basis of brightness at 60 µm and "warm" infrared color [f.(25 µm)lfv(60 µm) > 0.2], 12 have luminosities characteristic of quasars. These 12 ultraluminous objects have Seyfert spectra, and nine of them show morphological evidence for recent collisions or mergers-they plausibly represent a transition stage between cooler ultraluminous infrared galaxies and optical quasars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
510
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 540 publications
(549 citation statements)
references
References 4 publications
37
510
1
1
Order By: Relevance
“…These broad lines are generally seen at longer wavelengths (i.e., Hα and possibly Hβ), which sufferless from dust extinction and host-galaxy dilution, and may be reddened Type 1.8 and 1.9 AGNs, 21 rather than pure Type 1 AGNs, since higher-ionization lines such as Mg II are narrow or absent (e.g., Brusa et al 2015). These reddened AGNs are an interesting class of objects, and at least some appear to be in a transition stage between an obscured and unobscured phase within the merger-induced galaxy/black hole co-evolution paradigm (Sanders et al 1988;Hopkins et al 2005;Brusa et al 2010;Banerji et al 2012;Farrah et al 2012;Glikman et al 2012). Indeed, the Hubble Space Telescope followedup a handful of these objects and revealed that they live in trainwreck host galaxies, indicative of merger activity (Urrutia et al 2008;Glikman et al 2015).…”
Section: Selecting Reddened Broad-lined Agnsmentioning
confidence: 99%
“…These broad lines are generally seen at longer wavelengths (i.e., Hα and possibly Hβ), which sufferless from dust extinction and host-galaxy dilution, and may be reddened Type 1.8 and 1.9 AGNs, 21 rather than pure Type 1 AGNs, since higher-ionization lines such as Mg II are narrow or absent (e.g., Brusa et al 2015). These reddened AGNs are an interesting class of objects, and at least some appear to be in a transition stage between an obscured and unobscured phase within the merger-induced galaxy/black hole co-evolution paradigm (Sanders et al 1988;Hopkins et al 2005;Brusa et al 2010;Banerji et al 2012;Farrah et al 2012;Glikman et al 2012). Indeed, the Hubble Space Telescope followedup a handful of these objects and revealed that they live in trainwreck host galaxies, indicative of merger activity (Urrutia et al 2008;Glikman et al 2015).…”
Section: Selecting Reddened Broad-lined Agnsmentioning
confidence: 99%
“…One direct way to test the model presented by Sanders et al (1988b) observationally is to probe this evolutionary sequence at the 'transition stage' where the youthful QSOs are just beginning to shed their cocoons of gas and dust (e.g. Coppin et al 2008;Simpson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ultraluminous infrared galaxies (ULIRGs) have been found to be ubiquitously strong, interacting merger systems heated by star-forming and/or AGN power sources (e.g., Genzel et al 1998). They have been hypothesized to evolve into normal quasars after the central engine clears away the dust associated with the massive burst of star formation (Sanders et al 1988;Sanders & Mirabel 1996;Veilleux 2006). These objects are possibly the first observational snapshot in merger evolution and formation of a larger elliptical galaxy.…”
Section: Introductionmentioning
confidence: 99%